Theoretical Study of Energetic Complexes （Ⅲ）： Bis-（5-nitro-2Htetrazolato-N2）tetraammine Cobalt（Ⅲ） Perchlorate （BNCP） and Its Transition Metal （Ni/Fe/Cu/Zn） Perchlorate Analogues - 尚静 张建国 张同来 黄辉胜 张绍文 舒远杰 (中国化学：英文版, 2012)
The geometric conformation and electronic structure of bis-（5-nitro-2H-tetrazolato-N2）tetraammine cobalt（Ⅲ） perchlorate and its Ni/Fe/Cu/Zn analogues are studied under the TPSS （Tao-Perdew-Staroverov-Scuseria） levels of density functional theory in order to throw light on the relationship between their energy gaps and impact sensitivity While the perchlorate ions are coordinated with the copper cation, which is different from the other four compounds NBO （Natural bond orbital） analyses indicated that the metal-ligand interaction in the Co complex is covalent, while the others are ionic. The analysis of the electrostatic potential demonstrated that the O atoms from the nitro-tetrazole ring and perchlorate were primarily negative, while the other atoms were positive. The study was also conducted to gain a better understanding of the correlation of the energy gap and impact sensitivity.